Late-Onset Ictal Asystole and Falls Related to Severe Coronary Artery Stenosis: A Case Report - Fortunato, Francesco; Labate, Angelo; Trimboli, Michele; Spaccarotella, Carmen; Indolfi, Ciro; Gambardella, Antonio (Frontiers in Neurology, 2022)
Introduction: Ictal asystole (IA) is a rare, underestimated and life-threatening cause of transient loss of consciousness and fall. Current treatment options for IA usually include cardiac pacemaker implantation. We report, for the first time, a case of IA related to coronary stenosis that resolved after coronary angioplasty. Case Presentation: A 73-year-old man had a 2-year history of dyscognitive seizures. Three months before our observation, he started to have sudden falls resulting in injury on several occasions. General and neurological examinations, and brain MRI were unremarkable. Interictal EEG showed bitemporal spiking. Ictal video-polygraphy revealed a theta rhythmic slowing over the temporal regions bilaterally. After seizure onset, the ECG showed sinus bradycardia, followed by sinus arrest that was associated with the patient’s fall from the standing position. Afterwards, sinus rhythm returned spontaneously. A diagnosis of IA was made. A comprehensive cardiologic evaluation revealed a sub-occlusive stenosis of the left anterior descending artery. Successful coronary angioplasty resolved IA, levetiracetam was added, and no seizure or fall has occurred in the following 14 months. Conclusion: The present case was unique as IA resolved after successful coronary angioplasty; in this way it highlights the importance of carefully investigating epilepsy patients with falls, to look for cardiac etiologies that are amenable to specific treatment. Awareness of this previously unrecognized triggering relationship has important implications for treatment and prognosis, especially in the elderly, since epilepsy and seizure-induced falls are common in older adults, as also cardiac and autonomic changes are more frequently seen in old age.